Epidemiological, clinical, and genotypic characteristics of pediatric Mycoplasma pneumoniae infections: an 8-year survey in Suzhou, China in the pre- and post-COVID-19 eras - Xu, Lina; Wang, Pengli; Wang, Yufeng; Liu, Bingjie; Xu, Xuena; Yang, Quying; Gao, Chunyan; Sun, Huiquan; Xu, Yuejuan; Xu, Qiuyan; Hao, Chuangli; Jiang, Wujun (Frontiers in Microbiology, 2024)
Abstract Objective: This study examines the epidemiology of Mycoplasma pneumoniae (M. pneumoniae) infections among children in Suzhou, China, during various pandemic phases. The goal is to discern evolving epidemic trends and to furnish robust evidence for clinical diagnosis and treatment. Methods: From January 1, 2016, to December 31, 2023, 113,625 consecutive patients with respiratory infections from three hospitals in Suzhou, China (Children's Hospital of Soochow University, Children's Hospital of Wujiang District, and Affiliated Suzhou Hospital of Nanjing University Medical School), were retrospectively enrolled in a surveillance study. Additionally, in 2023, children hospitalized with M. pneumoniae pneumonia at the Children's Hospital of Soochow University were tested for genotype (P1 gene typing, SNP genotyping) and macrolide resistance in their bronchoalveolar lavage fluid. Results: From 2016 to 2023, the M. pneumoniae positive detection rate among pediatric respiratory infections fell from a pre-pandemic 21.1% to pandemic lows, then surged to 45.3% post-pandemic. Before the pandemic, peak M. pneumoniae infection rates occurred in summer, followed by autumn. Post-pandemic, the highest peak rates were in autumn.Peak M. pneumoniae detection rates occurred in 2019 and 2023, with a notable increase in children aged 6 and older in 2023. In this study, 200 M. pneumoniae-positive bronchoalveolar lavage fluid (BALF) cases in 2023 were randomly selected and analyzed for P1 genotype and SNP genotype. Among 156 cases, 81.4% were P1 genotype and 18.6% were P2 genotype. The proportion of severe M. pneumoniae pneumonia with the P1 type was significantly higher than that with the P2 type (P < 0.05).Of the 192 samples analyzed, 11 SNP genotypes were identified, with SNP-27 predominating (36.5%), followed by SNP-0 (21.4%), SNP-11 (18.8%), and SNP-34 (17.7%).Of the 192 BALF specimens, 97.3% exhibited macrolide resistance mutations, with A2063G mutations at 96.17%. The mutation rates for the 23S rRNA 2064 and 2617 were 1.6% and 1.0%, respectively. Conclusions: Post-COVID-19 in Suzhou, China, M. pneumoniae infection patterns shifted significantly, with initial NPIs-induced declines followed by a sharp rise in cases, especially impacting school-age children. This trend underscores the importance of ongoing epidemiological surveillance and the development of strategic public health responses.